2023
DOI: 10.1071/is22030
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitan abyssal lineages? A systematic study of East Pacific deep-sea squat lobsters (Decapoda: Galatheoidea: Munidopsidae)

Abstract: Munidopsid squat lobsters are among the most abundant decapods at abyssal depths and the most diverse squat lobster group in the East Pacific region. During recent cruises along the East Pacific, many deep-sea squat lobsters were collected. Among these, we described five new munidopsid species supported both by morphological characters and molecular phylogenetics: Munidopsis girguisi sp. nov., M. nautilus sp. nov., M. testuda sp. nov., M. cortesi sp. nov. and M. hendrickxi sp. nov. We also report new records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The mitochondrial COI gene is considered as rather conservative in the genus Munidopsis between populations and among sibling species (cf. Jones and Macpherson 2007 ; Thaler et al 2014 ; Coykendall et al 2017 ; Dong et al 2019 ; Rodríguez-Flores et al 2023 ). Thus, the phylogenetic hypothesis based on COI data by Rodríguez-Flores et al (2023) concluded that M. albatrossae and M. aries , as well as many other abyssal species of this genus, are not distinguished as different species.…”
Section: Taxonomic Accountmentioning
confidence: 99%
See 3 more Smart Citations
“…The mitochondrial COI gene is considered as rather conservative in the genus Munidopsis between populations and among sibling species (cf. Jones and Macpherson 2007 ; Thaler et al 2014 ; Coykendall et al 2017 ; Dong et al 2019 ; Rodríguez-Flores et al 2023 ). Thus, the phylogenetic hypothesis based on COI data by Rodríguez-Flores et al (2023) concluded that M. albatrossae and M. aries , as well as many other abyssal species of this genus, are not distinguished as different species.…”
Section: Taxonomic Accountmentioning
confidence: 99%
“… Jones and Macpherson 2007 ; Thaler et al 2014 ; Coykendall et al 2017 ; Dong et al 2019 ; Rodríguez-Flores et al 2023 ). Thus, the phylogenetic hypothesis based on COI data by Rodríguez-Flores et al (2023) concluded that M. albatrossae and M. aries , as well as many other abyssal species of this genus, are not distinguished as different species. Nevertheless, such low genetic divergences may be more apparent than real because increasing depth could reduce the rate of substitution ( Rodríguez-Flores et al 2022b ).…”
Section: Taxonomic Accountmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous later studies have shown that the abyssal fauna has a rich species diversity and the cosmopolitan distribution of many species is contentious (e.g. 12 17 ). The extent of geographic range may influence species ability to recover after disturbance but at the same time wrong estimation of such range may lead to overestimation of the resilience potential of certain taxon.…”
Section: Introductionmentioning
confidence: 99%